RESPON PERTUMBUHAN DAN HASIL LIMA GENOTIP PADI HIBRIDA TERHADAP PUPUK ORGANIK TANDAN KOSONG KELAPA SAWIT (TKKS) PADA TANAH ULTISOL - David Khairullah Hadi; Reny Herawati; Widodo Widodo; Mukhtasar Mukhtasar; Helfi Eka Saputra; Eko Suprijono (BPFP Universitas Bengkulu, 2020)
[RESPONSE OF GROWTH AND YIELD OF FIVE RICE HYBRID GENOTYPE ON THE ORGANIC FERTILIZER OF PALM OIL BUNCHES ON ULTISOL]. Oil Palm Bunches (OPB) are solid waste potential as organic fertilizer to improve soil physical, biological and chemical properties, especially on ultisol soils for rice development. This research was conducted in August - November 2019 in Padang Harapan, Bengkulu City. The materials used were F1 rice seeds, OPB organic fertilizer. The experimental design was a factorial Randomized Completely Block Design (RCBD) with 2 factors. The first factor was 5 hybrid genotypes (F1), namely, Kuning x Inpago5, Kuning x Inpago9, Kuning x Inpago6, Arang x Inpago8, and Kuning x Salumpikit. The second factor was the dosage of OPB, namely 0 (control), 10 tonnes/ha, 15 tonnes/ha, and 20 tonnes/ha, the experiment was repeated 3 times. The variables observed were plant height, number of productive tillers, flowering age, harvest age, the total number of fill grains, number of filled grains, number of empty grains, 1000 grain weight, and grain weight/hill. The results showed that there was an interaction between genotype and OPB on the number of tillers. The interaction between the Kuning x Salumpikit genotypes and 10 tonnes/ha of organic fertilizer produced the largest number of tillers. Genotype G3(Kuning x Inpago6) produced the best rice growth and yield. In this study, the optimum point for OPB fertilization on growth and yield of the five genotypes tested had not been obtained.